Traditional vs. innovative uses of computers among mathematics pre-service teachers in Serbia. Issue 7 (3rd October 2017) - Teo, Timothy; Milutinović, Verica; Zhou, Mingming; Banković, Dragić
ABSTRACT: This study examined pre-service teachers' intentions to use computers in traditional and innovative teaching practices in primary mathematics classrooms. It extended the technology acceptance model (TAM) by adding as external variables pre-service teachers' experience with computers and their technological pedagogical content knowledge (TPCK). Data collected from 226 participants revealed that the proposed model had a good fit for both traditional and innovative uses of computers. Structural equation modelling suggested that the established TAM variables, together with TPCK and experience, were significant determinants of pre-service teachers' intentions to use computers in teaching mathematics at both levels. The most dominant determinant of behavioural intention was TPCK, followed by attitude. The proposed model explained 22.7% of the variance in the use of computers in traditional teaching practices and 27.6% of the variance in the use of computers in innovative teaching practices. The implications for mathematics teaching are discussed in the final section.